Pengaruh Pemberian Pakan Alami yang Berbeda terhadap Pertumbuhan dan Kelangsungan Hidup Larva Ikan Nila (Oreochromis niloticus) The - Agnes Kartika Silaban; Syammaun Usman (AQUACOASTMARINE, 2018)
Tilapia fish (Oreochromis niloticus) is one of the most widely cultivated freshwater fish species in Indonesia. The main problem in the cultivation of tilapia fish is mostly caused by the high number of mortality at the larvae stage which is largely due to the unavailability of the right feed. Natural feed is the most suitable feed used as larvae feed because it is easily digested and contains proteins that support the growth of larvae. This study aims to determine the effect of different natural feeding on the growth and survival of tilapia larvae. The method used in this study was a Complete Randomized Design (CRD) with three treatments and three replications: Tubifex sp. (T), Daphnia sp. (D) and Infusoria (I). The results showed the highest growth was in the treatment Tubifex sp. (T) with a length of 2,1 cm and an increase of weight is 0,31 gram, followed by Daphnia sp. (D) with a length of 1,6 cm and an increase of weight is 0,24 gram, and the lowest growth was in the Infusoria (I) treatment with 1,3 cm in length and 0,21 gram weight increase. The highest survival rate was found in Tubifex sp. (T) 93,06 %, then Daphnia sp. (D) 90,28 %, and the lowest in Infusoria treatment (I) 84,72 %. Feeding with different natural feed effect the growth of fish, but do not effect the survival rate of tilapia fish larvae.Keywords : Natural Feed, Fish Tilapia Larvae, Growth, Survival